Administrative reforms: Lessons and experiences - Srinivas, V. (The Journal of Governance)
The Governance landscape of India has radically changed in scale, scope and learning paradigms. India has succeeded in transforming technologically obsolete institutions into modern day digital institutions which benefit millions of Indians. Today India$1 (Bs rural country side has changed - banking Correspondents, e-Mitras and common service centers have bridged the gap between internet poor and internet rich. As India celebrates its 75th year of Independence as Azadi ka Amrut Mahotsav, the Prime Minister has given a clarion call for adoption of Next Generation Reforms by bridging the gap between government and citizens. This vision of Next Generation administrative reforms of the Prime Minister has been diligently translated into reality by Department of Administrative Reforms and Public Grievances (DARPG). Secretariat Reforms, Swachhta Campaigns, Benchmarking of Governance and Services, Redressal of Public Grievances & Improving Service Delivery, recognizing meritocracy and replication of good governance practices form the core of India$1 (Bs good governance model.- Reproduced s